Regular antilattices - Cvetko-Vah, Karin (The art of discrete and applied mathematics, 2019)
Obravnavamo in preštevamo antimreže ?$(S; \vee, \wedge)$?, za katere so Greenove ekvivalence ?$\mathcal{L}_{(\vee)}$?, ?$\mathcal{R}_{(\vee)}$?, ?$\mathcal{L}_{(\wedge)}$? in ?$\mathcal{R}_{(\wedge)}$? tudi kongruence na celotni antimreži.
Keywords: antilattice; antimreža; composition; enumeration; Greenove ekvivalence; Green's equivalences; kompozicija; lattice of subvarieties; mreža podraznoterosti; nekomutativna mreža; noncommutative lattice; particija; partition; preštevanje